Case Report: Analysis of Drug Related Problems (DRP's) in Patients with Hepatic Cirrhosis PNSD Ctp B, Chronic Hepatitis B, Dyspepsia Syndrome, Hypoalbuminemia and Hepatic Function Disorders - Husnawati, Husnawati; Aradziluna, Dian; Bidriah, Mutia (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Liver cirrhosis is a chronic liver disease characterized by fibrosis and replacement of normal liver tissue with abnormal nodules. The main etiologies include hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, alcohol-related liver disease, and non-alcoholic fatty liver disease (NAFLD). The prevalence of liver cirrhosis based on autopsy findings is around 2.4% in Western countries, while in the United States it is estimated at 360 per 100,000 population, causing approximately 35,000 deaths annually. Objective: This case report aims to describe the treatment and identify drug-related problems (DRPs) in a patient diagnosed with PNSD CTP B liver cirrhosis, chronic hepatitis B, dyspepsia syndrome, hypoalbuminemia, and impaired liver function. Method: This study employed a case report design with primary data obtained from patient interviews and retrospective documentation review. Data were analyzed using the SOAP method to identify DRPs. Results: The analysis revealed minor drug interactions, including spironolactone–furosemide, tenofovir disoproxil fumarate (TDF)–morphine sulfate tablet (MST), and cefixime–furosemide. Conclusion: Patients with complex comorbidities are at increased risk of DRPs. Continuous pharmacotherapy monitoring is essential to minimize toxicity and adverse effects.